The role of unmet demand in the dynamics of energy supply forms: The case of electricity market structures in sub-Saharan Africa - (:unkn) unknown (My University, 2017)
The energy sector in sub-Saharan Africa is in a state of flux. Based on an approach borrowed from industrial economics, using historical examples that point to three successive transformations of electricity market structure, our analysis differs from previous studies by looking at demand as a consequence of supply. Our results show, an extremely fragmented demand for energy in sub-Saharan African countries, within which a very dynamic unmet demand drives change in how supply is offered. New forms of energy provisioning introduced on the electricity market put into question the initial ongrid network model. The appearance of decentralized electricity production shows that there is a potential for going beyond current limitations and moving away from a supply structure focused on the maintenance and improvement of on-grid networks without consideration of the needs of rural populations on one hand, and on the other hand, the establishment of expensive mini-grids that provide inferior energy services to rural populations. New territorial linkages focus on mechanisms seen in energy demand.
Keywords: African Research